Restocking Herbivorous Fish Populations As a Social-Ecological Restoration Tool in Coral Reefs - Abelson, Avigdor; Obolski, Uri; Regoniel, Patrick; Hadany, Lilach (Frontiers in Marine Science, 2016)
The degradation of the world's coral reefs has aroused growing interest in ecological restoration as a countermeasure, which is widely criticized, mainly due to cost-effectiveness concerns. Here, we propose the restocking of herbivorous fish as a restoration tool, based on supply of young fish to degraded reefs, with the aims of: 1. Buildup of a critical fish biomass for basic ecosystem functions (e.g. grazing); 2. Increased fishing yields, which can sustain coastal communities, and consequently; 3. Reduced reef destruction and better local compliance with fishery policies. We present the rationale of the restocking approach as both a reef restoration and a fishery management tool, and examine its pros and cons. This approach requires, however, further social-ecological and aquaculture research in order to support the critical stages of its implementation.